Content Accuracy and Recency of TPACK-Based Physics Textbooks on Work and Energy Materials to Improve Science Literacy of High School Students - Zidan Afidah; I Ketut Mahardika; Subiki (Yayasan Nurul Yakin Bunga Tanjung, 2023)
TPACK-based textbooks are reference books containing a collection of material from certain branches of knowledge that are presented comprehensively using a combination of pedagogic technologies and content that are applied according to the learning context. Scientific literacy is the scientific ability possessed by students to solve various kinds of problems and explain scientific phenomena scientifically. Work and energy are physics materials closely related to students' daily lives. The method used for this research is to use research and development research and development methods. Based on the results of the latest and contextual material validation on the suitability of the material with the latest scientific developments, validator one scores four, and validator two scores 4. The 100% percentage results that meet the criteria are very valid. From the results of the validation assessment in terms of the average rating of each validator for the two validators, an average percentage result of 87.49% is obtained with very valid criteria. This shows that the TPACK-based physics textbook on the subject matter of work and energy is appropriate to be used as an Electronic School Book aid for students in understanding and mastering material about work and energy.